2017
DOI: 10.4103/jnrp.jnrp_173_17
|View full text |Cite
|
Sign up to set email alerts
|

How Long does Denervation Take in Poliomyelitis? Or is it a Lifetime?”

Abstract: Background and Objective:This study aims to determine the period of reinnervation in patients with poliomyelitis. This research was conducted to identify the appearance of denervation potentials in patients with poliomyelitis as indicators for reinnervation.Materials and Methods:A total of 246 male patients with poliomyelitis were assessed electrophysiologically between 1988 and 2007. The mean age was 22.8 (18–42). It has been an average of 19.9 ± 4.9 years since the beginning of complaints from the patients.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…These findings were consistent with the literature [5]. Presence of active denervation findings in EMG can be seen in patients with poliomyelitis, and it is known that detection of active denervation is not used to differentiate patients with post-polio syndrome from those without [5,15,16].…”
Section: Discussionsupporting
confidence: 91%
“…These findings were consistent with the literature [5]. Presence of active denervation findings in EMG can be seen in patients with poliomyelitis, and it is known that detection of active denervation is not used to differentiate patients with post-polio syndrome from those without [5,15,16].…”
Section: Discussionsupporting
confidence: 91%
“…This finding was important since it showed that the bulbar region was affected slightly. Similar to the literature, in our study, 28% of patients and 6% of the muscles examined showed signs of active denervation [17]. Active denervation findings were mostly observed in the medial gastrocnemius muscle.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, PSWs or FPs were present in 23.5% of the patients. 7 However, unlike our study, patients with radiculopathy were not included in the study of Şenol et al Only one patient with PSWs/FPs did not have a lumbosacral MRI, and most of the remaining patients with PSWs/FPs had concordant nerve segments of muscles with these active denervation findings and radiculopathy segments found on MRI. Considering that patients with radiculopathy were not included in the study by Şenol et al, a higher rate of PSWs/FPs was observed compared to our study.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, active denervation findings such as PSWs/FPs may be present even after years of poliomyelitis. [5][6][7] In this current study, PSWs/FPs were investigated in polio survivors with sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation